When municipalities become larger: the short-term and more long-term consequences for local democracy - Hansen, Sune Welling; Hjelmar, Ulf (Politica, 2015)
We examine the relationship between the size of a local political system and the state of the local democracy in the system, using the 2007 Danish municipal mergers as a quasi-experiment. Our study is informed by a number of recent studies that use the same approach. We make two contributions to this literature: We examine a broad set of dimensions in the state of the local democracy, and we examine both the short-term consequences (two years after their implementation) and the more long-term consequences (six years after) of the increases in municipal size created by the mergers, although the latter results should be interpreted cautiously. Our analyses show that citizens’ assessments of their local democracy are very robust to changes in municipal size and only on a few dimensions do we find supporting evidence for systematic changes in the short term and the longer term.